Identification and Analysis of Influential Factors in Good Rural Governance (Case Study: Ardabil County) - Kiumarth Khodapanah (برنامه ریزی فضایی, 2022)
AbstractProblem definition: Rural governance is a new process in the rural management system, which has different principles, criteria, and indicators, as well as many players in the rural field.Purpose: The present study was conducted with the aim of investigating the influence of Shura, Dehiari, Agricultural Jihad, Housing Foundation, etc. in the rural governance of Ardabil County.Methodology: This research was practical in terms of purpose with a descriptive-analytical nature. The statistical population included 30 experts and specialists in the rural field. The sampling method was targeted at the beginning and followed by snowball sampling. Mactor software was used to analyze the issue. 9 actors and 9 targets were analyzed in the software and the degrees of effectiveness, competitiveness, convergence, agreement, and divergence between the actors were investigated.Results: The results showed that the actors’ performances played an important role in determining and achieving goals. The highest number of effects (111) was related to social networks. The highest level of competitiveness (2.05) was related to social networks. The goal of governance accountability also had the highest level of agreement between the actors.Innovation: In this research, for the first time, analysis of the key factors of rural governance was done by using the Mactor technique. IntroductionGovernance is a reform that, with its specific complexities, indirectly tries to change the main and centralized view of the government towards network-based participatory policy-making. It is one of the pluralist tools moving towards a unified society. Rural sustainability is considered as the ultimate ideal of this model. One of the basic solutions of governance is sustainable rural planning and management. Taking into account the influential role of desirable and worthy management in all dimensions leads to the adoption of strategies and solutions that provide the role of participatory management. For this purpose, this research intended to use Mactor software. The key actors influencing rural governance with their relative strengths, goals, and priorities had to be identified. By evaluating the convergence between them, the possibility of realizing a different future could be provided. In this way, by properly organizing and strengthening management systems that were based on people's participation and determination, it was possible to take important steps in the path of reconstruction, while more useful management of the rural community of Ardabil County could be achieved through the participations and cooperation of governmental, non-governmental, and public institutions. Research MethodThe current research was applied in terms of purpose and was based on descriptive-analytical nature. The approach governing this research was a mixed method. The statistical population of the study was made up of the experts and elites in the field of rural management and governance. Therefore, in this research, some specialists, experts, and faculty members were selected in a targeted manner. By using the snowball sampling method, they were asked to introduce the next person. Extraction of the hidden and visible actors in the process of rural management was done by using an open questionnaire in the Delphi form. After collecting the actors and their objectives, in the second step, the matrix of the mutual effects of the indicators in the rows and columns was formed in Excel and entered into Mactor software. Mactor technique had to be done in 8 steps: 1) identification of the actors and goals; 2) matrix of the mutual effects; 3) effects of the goals and actors on each other; 4) performance analysis; 5) competitive power; 6) position of the maximum matrix; 7) convergence and divergence; 8) actors’ agreement. Results and discussionThe findings showed the degrees of influence and effectiveness of the actors' performances on each other. The highest level of influence was related to social networks with a numerical value of 111 and the greatest degree of effectiveness was related to Islamic council with 17 number of effects. In the second place, there were fertilizers with an effectiveness level of 100. The most level of effectiveness was related to the Islamic council and villagers with 16 effects. In relation to the competitiveness of the 9 considered actors, social networks with a rate of 2.05 had the most level of competitiveness among the players in the field of governance. The rank of universities was 1.62. On the other hand, the goals of participation, justice, accountability, legality, responsibility, and transparency were considered as the common goals of the actors with an agreement value of 9. Examining the positions of the actors involved in rural governance based on the considered goals showed that the highest levels of agreement among the actors were related to the goals of accountability, legality, justice, equality, and comprehensiveness. Concerning the actors’ agreements on the goals, the goal of responsibility was at the top and the lowest level of their agreement was with the central consensus regarding the goal of accountability, which indicated their disagreement between the actors on this goal. ConclusionActors’ performance has an important role in determining and achieving goals. As the findings of this study showed, actors, such as NGOs and social networks, were more effective than other actors. Also, the scope of their competitiveness was more than the other actors of Bodef, which indicated that these actors had a greater role in the field of rural governance. The analysis of the actors in the chart of influence and effectiveness showed that NGOs and social networks had the most influence and this indicated a weakness in the administrative system, which had disrupted the interaction cycle of actors. On the other hand, in terms of effectiveness, the highest level was related to organizations, such as Islamic council and Village Cooperative. These organizations, as the institutions in rural areas had to have the most interaction and convergence with other institutions. In addition to the level of influence, Shura and Dehiari had the lowest levels of competitiveness with other actors. It was possible to get rural citizens’ participation in the administration of village affairs. Their familiarity with the duties of the village council and other actors would make them aware of their roles and responsibilities. On the other hand, the organizations involved in the rural administration could provide the necessary conditions in this regard. Thus, with the cooperation and conscious participation of citizens and officials, the ground for their greater convergence in achieving the goals would be provided. Therefore, this approach of rural governance in the management of village affairs, was absolutely necessary and evident for strengthening the intended goals and convergence between the actors. Although the performance of social media and social networks played a greater role, the output and results showed all the actors’ agreement, which indicated convergence between all the actors. The actors did not disagree with or diverge from the set goals, but only the intensity and weakness of the effects varied. On the other hand, since the largest number of actors had the goal of ruling, no divergence was observed among them. Based on this, the actors in the field of rural governance prioritized the goals and finally, responsibility was prioritized. Keywords: Good Rural Governance, Key Actors, Goals of Rural Governance, MACTOR Software, Ardabil County References- Ahmadpour Dariani, M. (2005). Entrepreneurship, Definitions, Theories, and Models. 6th Edition, Tehran, Pardis Publishing Center. [In Persian]- Beer, A. (2014). Leadership and the Governance of Rural Communities. Journal of Rural Studies, 34(1), pp. 254–262.- Bezi, Kh., Keyani, A., Hanifi Assal, Y., Razi, A. (2011). Analysis of Spatial Differences of Social Capital in Bordering Urban and Rural Areas of the Country: Comparative Comparison of Urban and Rural Centers of Urmia City. Iranian Journal of Sociology, 11(2), pp. 74-102. [In Persian]- Daftary, D. (2019). Elected local bodies, space, and governance of market expansion in rural India. Geoforum, Vol. 103, pp. 105-113.- Eazidi, A. and Alavizadeh, S. A. M. (2018). Analysis of the Role of Psychological Empowerment of Villagers in the Process of Rural Management and Development (Case Study: Rashtkhwar District). Geographical Explorations of Desert Regions, 6(1), pp. 199-227. [In Persian]- Fal Suleiman, M., Shatri, M., & Khosravi, N. (2019). Comparative Study of Desirable Rural Governance Indicators (Case Study: Birjand County). Khorasan Cultural-Social Studies Quarterly, 15(1), pp. 95-118. [In Persian]- Faraji Sobkbar, H. A., Darban Astaneh, A., Akhavan Heydari, K., Madanlu Joibari, M., & Khatami, H. (2021). The Role of Good Governance in Facilitating Entrepreneurship Opportunities in Rural Areas (Case Study: Gamishan County). Economy of Space and Rural Development, 10(3), pp. 153-174. [In Persian]- Georgios, Ch. and Barraí, H. (2021). Social innovation in rural governance: A comparative case study across the marginalised rural EU. Journal of Rural Studies. Available online of the 11th of June, 2021 at https://doi.org/10.1016/j.jrurstud.2021.06.004- Hankins and Katherine B. (2009). Disappearance of the State from Livable Urban Spaces. Antipode, 41(5), pp. 845–866.- Heydari Sarban, V. (2018). Analysis of the Effects of Information and Communication Technology on Good Rural Governance (Case Study: Meshginshahr County). Spatial Planning (Geography), 8(3), pp. 41-64. [In Persian]- Heydari Sarban, V. (2019). Evaluation of the Local Rural Management Model Based on Good Governance Indicators (Case Study: Meshginshahr County). Geography and Development, No. 57, pp. 133-154. [In Persian]- Heydari Sarban, V., Arshadi, A., & Saeb, Sh. (2017). Evaluation of Governance Effects on the Development of Rural Tourism (Case Study: Nir County). Tourism Space, 7(25), pp. 33-50. [In Persian]- Khodapanah, K. (2021). Evaluation of the Effects of Competent Governance on the Livability of Villages (Case Study: The Central Part of Ardabil County). Regional Planning Quarterly, 11(41), pp. 83-100. [In Persian]- Lyall, C. and Tait, J. (2019). Beyond the Limits to Governance: New Rules of Engagement for the Tentative Governance of the Life Sciences. Research Policy, 48(5), pp. 1128-1137.- Maleki, S., Zarei, J., & Zadvali Khajeh, Sh. (2018). Evaluation of Desirable Urban Governance Indicators with a Neighborhood-Based Management Approach (Case Study: Neighborhoods of Hamadan City). Geography and Regional Urban Planning, 8(29), pp. 61-74. [In Persian]- Masroranjad, N., Moulai Hashjin, N., Pourramezan, E., & Ghoreishi, M. B. (2021). Explanation of Factors Affecting the Efficiency, Effectiveness of Management, and Rural Participation in the Development of Villages in Soumesara City with a Good Governance Approach. Human Geography Researches, 53(4), pp. 1523-1541. [In Persian]- Mengisteab, K. (2009). Good Governance in the Eritrean Context: What Does It Entail? Eritrean Studies Review, 2(2), pp. 20-57.- Merrell, I. (2022). Blockchain for decentralised rural development and governance. Journal Pre-proof. Available online on the 29th of April, 2022, Article 100086, doi: https://doi.org/10.1016/j.bcra.2022.100086- Najarzadeh, M., Torabi, Z. A., & Malekan, A. (2017). Investigating the Impact of Social Capital on Good Governance and Stability of Rural Communities with the Moderating Role of Cultural Capital (Case Study: Godin District, Kangavar County). Spatial Planning, 7(3), pp. 25-40. [In Persian]- Norouzi, A. and Ebrahimi, E. (2018). Realization of Good Governance Indicators in the Rural Areas of Lanjan County. Physical Development Planning, 3(6), pp. 93-109. [In Persian]- Pazaki, M., Sheikhi, D., & Samadi Moghadam (2020). Analysis of the Role of Management Based on Good Governance in Sustainable Rural Development (Case Study: Filistan District, Pakdasht County). Geography and Development, 58, pp. 112-93. [In Persian]- Pazaki, M., Sheikhi, D., & Zand, F. (2021). Examining the Place of Good Governance in the Development of Sustainable Rural Tourism (Case Study: Sorkheh County). Regional Planning, 11(43), pp. 64-78. [In Persian]- Ruknuddin Eftekhari, A. R. and Azimi Amoli, J. (2014). Rural Governance (Sustainable Development Management). Tehran, SAMT Publications. [In Persian]- Talshi, M., Darban Astane, A., & Mousavi, S. A. (2017). Explaining the Spatial Pattern of Good Rural Governance around Karaj Metropolis. Urban Planning Geography Researches, 5(4), pp. 585-606. [In Persian]- Wong, H. L., Wang, Y., Luo, R., Zhang, L., & Rozelle, S. (2017). Local governance and the quality of local infrastructure: Evidence from village road projects in rural China.  Public Economics, Vol. 152, pp. 119-132.- Woreda, S. H. (2017). An examination of the effectiveness of multi-dimensional decision-making methods: A decision-making paradox. Decision Support Systems, 5(3), pp. 303–312.- Xian, Sh. and GU, Z. (2020). The making of social injustice and changing governance approaches in urban regeneration: Stories of Enning Road, China. Habitat International, 98, pp. 1-11.- Xue, D. and Wub, F. (2015). Failing entrepreneurial governance: From economic crisis to fiscal crisis in the city of Dongguan, China. Cities, 43, 10–17.- Yang, H. (2021). Holistic Governance: An Explanatory Framework. In Urban Governance in Transition, pp. 57-95.